Development of Virtual Science Learning Media Assisted by Musschenbroek Tools on Length Expansion Material - Lugi, Fitriana (Balai Publikasi Indonesia, 2024)
This research was conducted in response to the lack of science learning media, particularly in physics materials, that can engage students' interest during the learning process. The purpose of this research is to develop virtual science learning media on the topic of linear expansion. The research method applied is research and development using the 4D model. In this study, a linear expansion tool was created. The research was conducted by developing a science e-module as learning media using the Flip Pdf application.